Effects of AM colonization on “wild tobacco” plants grown in zinc-contaminated soil - Audet, Patrick; Charest, Christiane (Université d'Ottawa | University of Ottawa, 2006)
This greenhouse study aimed to determine the effect of colonization by the arbuscular mycorrhizal (AM) fungus (Glomus intraradices Schenck & Smith) on the “wild” tobacco (Nicotiana rustica L. var. Azteca), under soil–zinc (Zn) conditions. Plants of N. rustica were grown in AM or non-AM inoculated substrate and subjected to four soil–[Zn] concentrations (0, 50, 100, and 250 mg Zn kg−1 dry soil). The AM root colonization increased markedly from 14 to 81% with the increasing soil–[Zn] and the mycorrhizal structures were significantly more abundant at the highest soil–[Zn], suggesting that Zn may be involved directly or indirectly in AM root colonization. In addition, total Zn content or Zn concentrations in shoots and roots were shown to increase as soil–[Zn] increased in both AM and non-AM plants. As for the growth parameters studied, there were no significant differences between treatments despite the increase in Zn content or concentration. The AM roots subjected to the highest soil–[Zn] had a significant reduction by about 50% of total Zn content and Zn concentration compared to non-AM roots. Still, the relative extracted Zn percentage decreased dramatically as soil–[Zn] increased. Soil pH was significantly lower in non-AM than AM treatments at the highest soil–[Zn]. In summary, AM plants (particularly roots) showed lower Zn content and concentration than non-AM plants. In this regard, the AM fungi have a protective role for the host plant, thus playing an important role in soil-contaminant immobilization processes; and, therefore, are of value in phytoremediation, especially when heavy metals approach toxic levels in the soil.
Keywords: Phytoremediation; Nicotiana rustica; Heavy metals; Glomus intraradices